2010
DOI: 10.1016/s1413-8670(10)70096-9
|View full text |Cite
|
Sign up to set email alerts
|

In vitro initial immune response against Leishmania amazonensis infection is characterized by an increased production of IL-10 and IL-13

Abstract: The initial encounter of Leishmania with its host's immune system is important in the outcome of infection. Previous studies have shown that PBMCs from healthy volunteers (HV) exposed to Leishmania differ in IFN-γ production. We have expanded such observations evaluating the profile and kinetics of cytokines (IFN-γ, IL-12p70, IL-10, IL-13), chemokines (CCL5, CCL3, CCL4, CXCL10), and chemokine receptors (CCR1,CCR5, CXCR3, CCR4) in vitro L. amazonensis-stimulated of HV's PBMCs. HVs were divided in groups of high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Conversely, it has been demonstrated that LbAg is a more potent stimulator of T cell response than LaAg in individuals infected with L. amazonensis , as well as in individuals infected with parasites from the Viannia subgenus, before and after therapy [49]. It has also been shown that LaAg or live L. amazonensis promastigotes are able to induce high levels of IL‐10 in PBMCs obtained from LaAg‐vaccinated volunteers [50] or from healthy subjects [51], suggesting that the differences observed between LbAg and LaAg stimulation can be related to suppressive factors that are triggered by L. amazonensis parasites. We could not detect CD4 + that were able to produce IL‐10 and IFN‐γ simultaneously and did not observe any differences in the frequency of IL‐10 + CD4 + T cells, or in CD4 + CD25 high IL10 + regulatory T cells between LbAg and LaAg stimulation (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, it has been demonstrated that LbAg is a more potent stimulator of T cell response than LaAg in individuals infected with L. amazonensis , as well as in individuals infected with parasites from the Viannia subgenus, before and after therapy [49]. It has also been shown that LaAg or live L. amazonensis promastigotes are able to induce high levels of IL‐10 in PBMCs obtained from LaAg‐vaccinated volunteers [50] or from healthy subjects [51], suggesting that the differences observed between LbAg and LaAg stimulation can be related to suppressive factors that are triggered by L. amazonensis parasites. We could not detect CD4 + that were able to produce IL‐10 and IFN‐γ simultaneously and did not observe any differences in the frequency of IL‐10 + CD4 + T cells, or in CD4 + CD25 high IL10 + regulatory T cells between LbAg and LaAg stimulation (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Upon stimulation with L . amazonensis , high IFN-γ producers also secrete more TNF [6], more IL-12 and less IL-13 [7]. These results indicate that a low IFN-γ response in vitro accompanies a slower IFN-γ production in vivo and authors suggested that in vitro responses could be used to predict, for example, the pace of post vaccination responses.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results, cytokines produced by the immune cells are effective on macrophage physiology and establish three populations of classic, alternative, and regulatory macrophages with different physiologies . Results of the previous studies indicated that in early stages of infection with L. major , macrophages can be activated through the alternative pathway, leading to the up‐regulation of TGFβ gene and arginase 1 enzyme as well as the down‐regulation of TNF‐α . It seems that OLE is able to increase the production of IFNγ and TNFα by activating classic macrophages.…”
Section: Discussionmentioning
confidence: 96%
“…They justify this finding as follows: In the early hours of infection, the Th 2 response is extremely active and the production of Th 2 ‐dependent cytokines is increased, while the secretion of Th 1 ‐dependent cytokines is decreased. Thus, the parasite survives in the macrophage, leading to the development of disease …”
Section: Discussionmentioning
confidence: 99%